2019
DOI: 10.1002/nau.24221
|View full text |Cite
|
Sign up to set email alerts
|

Regions of the brain activated in bladder filling vs rectal distention in healthy adults: A meta‐analysis of neuroimaging studies

Abstract: Aims: Adults with pelvic floor disorders commonly present with overlapping bladder and bowel symptoms; however, the relationship between urinary and defecatory dysfunction is not well understood. Our aim was to compare and determine if overlapping brain regions are activated during bladder filling and rectal distention in healthy adults. Methods: We conducted separate Pubmed searches for neuroimaging studies investigating the effects of rectal distention and bladder filling on brain activation in healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…In healthy subjects, the right insula has an interoceptive function of mapping visceral signals, mainly nociceptive inputs, and making them accessible to consciousness 32 and its activation appears to be increasing with bladder filling 19 . Halani et al 8 have also demonstrated through contrast analysis that both rectal and bladder filling among healthy subjects results in activation of the insula, hypothesizing its implication as a supraspinal center in the overlap of bowel and bladder symptoms in pelvic floor disorders. Moreover, in the study of Ketai et al 25 involving 53 OAB and 20 healthy subjects, a statistically significant difference in activation is noted at the level of the insula in OAB patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In healthy subjects, the right insula has an interoceptive function of mapping visceral signals, mainly nociceptive inputs, and making them accessible to consciousness 32 and its activation appears to be increasing with bladder filling 19 . Halani et al 8 have also demonstrated through contrast analysis that both rectal and bladder filling among healthy subjects results in activation of the insula, hypothesizing its implication as a supraspinal center in the overlap of bowel and bladder symptoms in pelvic floor disorders. Moreover, in the study of Ketai et al 25 involving 53 OAB and 20 healthy subjects, a statistically significant difference in activation is noted at the level of the insula in OAB patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The two most frequent techniques used are positron emission tomography (PET) and functional magnetic resonance imaging (fMRI), and at a lesser extent, single‐photon emission computed tomography (SPECT) 6 . These techniques rely on a local hemodynamic response based on the principle of neurovascular coupling where activated neuronal bundles requiring more oxygen and nutrients induce an increased blood flow in a region of interest (ROI) 7 normally reported in stereoscopic x , y , and z displacement coordinates 8 . Advancement in fMRI has also led to the development of newer techniques such as resting‐state functional connectivity MRI (rs‐fcMRI) requiring no specific task from the patient; on the contrary, exploring intrinsic neuronal functional connectivity at a resting state 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional imaging studies have shown neural control of bladder, bowel, and sexual function to be complex, involving many regions of the brain [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. HD is characterized by progressive neuronal loss in the basal ganglia, and atrophy has also been reported for frontal, temporal, insular, and parietal cortical areas in HD [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies focus on functional magnetic resonance images (fMRI) limited to only a handful of subjects [50,51]. While the sensation of bladder distention and urgency has been associated strongly with the thalamus in rats, human studies show involvement of a plethora of other structures [52][53][54][55].…”
Section: Central Pathwaysmentioning
confidence: 99%